Synthesis And Characterization Of Aluminium Based Nanomaterials Using Direct Heating Technique - Liong, Kai Min (Universiti Sains Malaysia, 2022)
The synthesis of aluminium based nanomaterials via direct heating technique was carried out in this research. Aluminium oxide (Al2O3) is a ceramic material with a wide bandgap (8.3 eV) that exhibits many unique properties such as high strength, good corrosion resistance, low thermal and electrical conductivity as well as high hardness, hence having a wide range of applications. Synthesis of Al2O3 nanomaterials were usually done through hydrothermal and chemical vapour deposition (CVD) methods, however these methods are mostly high energy consumption and time consumption. Hence, direct heating technique was developed in order to synthesize Al2O3 nanomaterials on kanthal wire with a much lower energy consumption rate and shorter duration. Synthesis parameters such as change in precursors, concentration as well as synthesis duration were systematically studied to determine the optimum parameter for Al2O3 nanomaterials formation. Various characterization methods such as X-ray diffraction (XRD), field emission scanning electron microscope (FESEM), transmission electron microscope (TEM) and UV-vis spectroscopy were used to characterize the as- grown nanomaterials. Nevertheless, the XRD analysis indicates that as-grown nanomaterials were Al-based, i.e. AlOOH and Al(OH)3 with average size of 568.3 ± 235.7 nm based on FESEM and 98.4 ± 35.8 nm based on the TEM result. The optimum synthesis parameter were determined to be 30 min synthesis duration using 0.008 mol of Al(NO3)3 precursor. The nanorods and nanoparticles formed have bandgaps of 3.03 and 3.57 eV respectively. Further works need to be done to further improve the synthesis condition of direct heating technique in order to obtain Al2O3 nanomaterial